Arthroscopic Versus Open Rotator Cuff Repair: Fellowship-Trained Orthopaedic Surgeons Prefer Arthroscopy and Self-Report a Lower Complication Rate - Blane C. Kelly, M.D; David S. Constantinescu, M.D; William Pavlis, B.S; Alexander R. Vap, M.D (Elsevier, 2021)
Purpose: To evaluate whether fellowship training had an effect on the practice pattern and complication rates among Part II examinees of the American Board of Orthopaedic Surgery (ABOS) for rotator cuff repair (RCR) from 2007-2017. Methods: The ABOS database was queried for arthroscopic (Current Procedural Terminology [CPT] code 29827) and open/mini-open (CPT codes: 23410, 23412) RCR performed from 2007-2017. Excluded were procedures that did not included CPT codes 29827, 23410, 23412. A comparison between arthroscopic and open/mini-open use as well as self-reported complications were assessed based on recorded fellowship training. Results: A total of 31,907 RCR were reported over the past 10 years (2007-2017). The percentage of RCR procedures performed using arthroscopic technique vs open/mini-open varied among surgeons who completed one fellowship: Sports Medicine (92.5 % arthroscopy; 7.5 % mini/open), Shoulder & Elbow (91.3 % arthroscopy; 8.7% mini/open), and Hand & Upper Extremity (69.6 % arthroscopy; 30.4 % open). Total complication rates varied among surgeons who completed one fellowship: Sports Medicine (11.5 %), Shoulder & Elbow (13.5 %), and Hand & Upper Extremity (13.4 %). Surgeons completing one fellowship in either Sports Medicine, Shoulder & Elbow, Hand & Upper Extremity all reported significantly lower complication rates using arthroscopic over mini/open technique (P < .001). Conclusions: Among ABOS Part II examinees completing a Sports Medicine, Shoulder and Elbow or Hand and Upper Extremity fellowship, Sports Medicine trained surgeons had significantly greater rates of performing arthroscopic over open RCR and significantly lower self-reported intraoperative complication rates. Clinical Relevance: Understanding the effects of fellowship training may guide mentors and future trainees.